Low yield of gastroscopy in patients with Lynch syndrome - Galiatsatos, Polymnia; Labos, Christopher; Jeanjean, Marie; Miller, Kyle; Foulkes, William D. (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Lynch syndrome (LS) is the most common hereditary colorectal cancer syndrome, caused by germline mutations in mismatch-repair genes. Besides a lifetime risk of colorectal cancer averaging 70%-80%, there is an increased risk of extracolonic tumors including gastric cancer. The utility of screening gastroscopy in Lynch syndrome has long been debated. This study aimed to determine the proportion of abnormal gastroscopies among patients screened, including the incidence of gastric cancer and prevalence of precursor lesions. Materials and Methods: Charts of patients with mutation-proven Lynch syndrome between January 1, 2004, and December 31, 2014, from the Genetics clinic and Hereditary Gastrointestinal Cancer Clinic of our institution were retrospectively reviewed. Results: A total of 66 Lynch syndrome patients were identified. Thirty-two gastroscopies were performed in 21 (32%) of them. No gastric cancers were found. The prevalence of precursor lesions (Helicobacter pylori gastritis, atrophic gastritis, and gastric intestinal metaplasia) was 19.05%. A family history of gastric cancer was associated with a non-significant increased risk of abnormal gastroscopy, while sex and specific gene involved did not affect the abnormality rate. Conclusion: Gastric screening in asymptomatic individuals with Lynch syndrome is probably best reserved for high-risk individuals, based on the family history and perhaps ethnicity as suggested by several governing bodies. Larger studies are required to achieve the statistical power necessary to address this controversial issue. Cite this article as: Galiatsatos P, Labos C, JeanJean M, Miller K, Foulkes WD. Low yield of gastroscopy in patients with Lynch syndrome. Turk J Gastroenterol 2017; 28: 434-8.